Cloning of a non-catalytic form of human trkB and distribution of messenger RNA for trkB in human brain. - Allen, S; Dawbarn, D; Eckford, S; Wilcock, G; Ashcroft, M; Colebrook, S; Feeney, R; MacGowan, S (1994)
A truncated form of the human trkB gene has been cloned and sequenced. This gene is related to the trk family of tyrosine kinases, the products of which act as receptors for the neurotrophins. Of these, brain-derived neurotrophic factor and mammalian neurotrophin-4 are the known ligands for the TrkB receptor. Catalytic and non-catalytic (or truncated) forms of the trkB gene have been cloned for rat and mouse. In this study, using in situ hybridization, we describe the distribution of trkB messenger RNA in fetal and adult human brain.